2020
DOI: 10.1093/sleep/zsaa056.1203
|View full text |Cite
|
Sign up to set email alerts
|

1209 Effect Of Wearables On Sleep In Healthy Individuals: A Randomized Cross-over Trial And Validation Study

Abstract: Introduction To determine whether a wearable sleep-tracker improves perceived sleep quality in healthy subjects. To test whether wearables reliably measure sleep quantity and quality compared to polysomnography. Methods A single-center randomized cross-over trial of community-based participants without medical conditions or sleep disorders. Wearable device (WHOOP, Inc.) that provided feedback regarding sleep information to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Supplementing the raw measurement data with other data makes the measurement, which is usually interpreted as a number, much more usable, but when supplemented with other data, the measurement result can be interpreted in context. [15]…”
Section: Smart Ecosystemsmentioning
confidence: 99%
“…Supplementing the raw measurement data with other data makes the measurement, which is usually interpreted as a number, much more usable, but when supplemented with other data, the measurement result can be interpreted in context. [15]…”
Section: Smart Ecosystemsmentioning
confidence: 99%
“…Smart watch that periodically sends biometric information such as body temperature and pulse rate to the center. Workplace level contact tracing wearable[ 16 ] …”
Section: Related Workmentioning
confidence: 99%
“…The wearable device has been adopted as an ideal means in the healthcare field due to its excellent ability to monitor the user’s stress level and physical fitness [ 14 ]. These include a smart watch[ 15 ] that periodically sends biometric information to the manager, a Bluetooth location beacons[ 16 ] that tracks the user’s location and contact, and a telemedicine[ 17 , 18 ] that allows clinicians to evaluate patient remotely. This wearable is characterized by being connected to an individual smartphone and periodically transmitting data by accessing the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] On the other hand, a particular wearable was studied in a clinical research that includes 32 participants and reported to be beneficial to improve the perceived sleep quality. [ 38 ] Although the factors such as feel and form factor greatly affects the user adoption of the wearables, these results points out that the clinical acceptance of a wearable strictly depends on its simultaneous accuracy on multiple patients. [ 39 ]…”
Section: Ppg and Optoelectronic Wearablesmentioning
confidence: 99%